2018
DOI: 10.1038/s41598-018-32116-8
|View full text |Cite
|
Sign up to set email alerts
|

Permissiveness to form pluripotent stem cells may be an evolutionarily derived characteristic in Mus musculus

Abstract: Mus musculus is the only known species from which embryonic stem cells (ESC) can be isolated under conditions requiring only leukemia inhibitory factor (LIF). Other species are non-permissive in LIF media, and form developmentally primed epiblast stem cells (EpiSC) similar to cells derived from post-implantation, egg cylinders. To evaluate whether non-permissiveness extends to induced pluripotent stem cells (iPSC), we derived iPSC from the eight founder strains of the mouse Collaborative Cross. Two strains, NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
11
1
Order By: Relevance
“…Companion resources including tissue and cell line biobanks are being generated for these populations. One emerging resource, a set of stem cell lines including mouse embryonic stem cells (mESCs) and induced pluripotent stem cells (iPSCs) derived from these populations [89,90], enables in vitro systems genetics and molecular phenotyping QTL validation.…”
Section: Resources For Discovery and Validationmentioning
confidence: 99%
“…Companion resources including tissue and cell line biobanks are being generated for these populations. One emerging resource, a set of stem cell lines including mouse embryonic stem cells (mESCs) and induced pluripotent stem cells (iPSCs) derived from these populations [89,90], enables in vitro systems genetics and molecular phenotyping QTL validation.…”
Section: Resources For Discovery and Validationmentioning
confidence: 99%
“…Similarly, different supplementation regimes are required for ESC and iPSC establishment in nonpermissive strains of mice. It has been suggested that the permissiveness to ESC derivation under relatively simple LIF conditions is an evolutionarily derived characteristic in M. musculus that is not shared with other eutherian mammals (Garbutt et al, ). This lack of effectiveness of protocols established in the standard murine and human ESC models is one of the main challenges for researchers working with domestic and exotic species.…”
Section: Discussionmentioning
confidence: 99%
“…Human ESC can be transformed to a state similar to mouse ESC by activating the LIF/ STAT3 pathway, but human ESC will differentiate if support from the MEK/ERK pathway is removed (Nichols & Smith, 2009;Rossello, Pfenning, Howard, & Hochgeschwender, 2016). In cats, neither supplementation of LIF nor fibroblast growth factor 2 (FGF2) supported the long-term maintenance of pluripotency in cells derived from ICM (Gómez et al, 2010;Yu et al, 2008;Zhou et al, 2019) that is not shared with other eutherian mammals (Garbutt et al, 2018). This lack of effectiveness of protocols established in the standard murine and human ESC models is one of the main challenges for researchers working with domestic and exotic species.…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of available model organism GRPs, and ultimately the choice of GRP depends not only on the ability of that organism to appropriately and economically model a particular disease but also on the diversity, strength, and haplotype structure of the alleles segregating in the population. Cellular GRPs can be created by deriving cell lines ('in vitro') or culturing primary cells ('ex vivo') directly from a genetically diverse population, thereby capturing the resident natural variation in those individuals [10][11][12][13]. The development and application of these cellular panels are active areas of genetic resource and technology development.…”
Section: Cellular Models From Grpsmentioning
confidence: 99%